2017
DOI: 10.1080/13625187.2017.1317339
|View full text |Cite
|
Sign up to set email alerts
|

The use of cyproterone acetate/ethinyl estradiol in hyperandrogenic skin symptoms – a review

Abstract: Introduction: Hyperandrogenism affects approximately 10-20% of women of reproductive age. Hyperandrogenic skin symptoms such as hirsutism, acne, seborrhea and alopecia are associated with significant quality of life and psychological impairment. Women with abnormalities in androgen metabolism may have accompanying anovulation and/or polycystic ovary syndrome (PCOS), both of which have reproductive and metabolic implications if left untreated. Cyproterone acetate (CPA), combined with ethinylestradiol (EE), is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
(103 reference statements)
0
10
0
1
Order By: Relevance
“…Since CPA has partial AR agonistic activity and is known as a mild AR antagonist, it is meanwhile rarely used in PCa hormone therapy [66]. Rather, CPA is clinically more used as birth control pills and in the treatment of androgen-dependent conditions such as acne and excessive hair growth [67]. CPA antagonism is dependent on co-repressor binding to the AR.…”
Section: Ar Antagonist-induced Cellular Senescencementioning
confidence: 99%
“…Since CPA has partial AR agonistic activity and is known as a mild AR antagonist, it is meanwhile rarely used in PCa hormone therapy [66]. Rather, CPA is clinically more used as birth control pills and in the treatment of androgen-dependent conditions such as acne and excessive hair growth [67]. CPA antagonism is dependent on co-repressor binding to the AR.…”
Section: Ar Antagonist-induced Cellular Senescencementioning
confidence: 99%
“…Clinical trials (mostly open-label comparator studies conducted between 1985 and 2012) show a high efficacy of CPA/EE in the treatment of hyperandrogenic skin symptoms in women with PCOS as discussed in the accompanying publication. The use of CPA/EE in hyperandrogenic skin symptoms -A review [49].…”
Section: Ultrasoundmentioning
confidence: 99%
“…The risk of VTE is generally reported to be higher with CPA/EE than with o pre-treatment may improve pregnancy outcomes (further studies needed) Figure 6. Benefits of CPA/EE in the treatment PCOS [37,49,51,[73][74][75].…”
Section: Risks Of Treatmentmentioning
confidence: 99%
“…[ 100 ] A nonsystematic narrative review based on a literature search of the PubMed database showed high efficacy of CPA 2 mg/EE 35 μg in the treatment of severe acne and hirsutism. [ 111 ]…”
Section: Hoice Of O Ral C mentioning
confidence: 99%